Mangrove vegetation structure in the Marine Science Techno Park (MSTP) Area, Teluk Awur, Jepara Regency, Central Java - Azzahra, Aliya Ikrimah; Jumari, Jumari; Utami, Sri (Bioma : Berkala Ilmiah Biologi, 2025)
Marine Science Techno Park (MSTP) is an area located in the Teluk Awur Beach region, Jepara Regency, Central Java. This area features a rehabilitated mangrove ecosystem that has been established for approximately 20 years. This research aims to study the mangrove vegetation structure, including diversity, composition, evenness index, Importance Value Index (IVI), and assess the regeneration of true mangroves in the Marine Science Techno Park (MSTP) area in Teluk Awur, Jepara, Central Java. The study was conducted at 3 stations: the mangrove track area (Station 1), riverbank area (Station 2), and coastal area (Station 3). The research identified 20 mangrove species (5 major mangroves, 4 minor mangroves, and 11 associated mangroves) belonging to 15 families. The species diversity index (H') ranged from 1.51 to 1.68, indicating a moderate category, while the evenness index indicates relatively even evenness ranging between (0.63 – 0.69), indicating relatively even communities and stable populations. The highest INP at station 1 (mangrove track) is Rhizophora mucronata Lamk (INP 163.58%), at station 2 (riverbank) is Bruguiera cylindrica (L) BI (INP 150.52%). At station 3 (coastline) the highest INP is Rhizophora mucronata Lamk (161.07%). The regeneration status of true mangroves in the MSTP area, categorized as good, includes Xylocarpus granatum Koen, Bruguiera cylindrica (L) BI, Ceriops tagal (Perr.) C.B. Rob, Rhizophora apiculata BI, and Rhizophora mucronata Lamk, while poor regeneration was observed in Nypa fruticans Wurmb, Lumnitzera racemosa Willd, Excoecaria agallocha L, and Aegiceras corniculatum (L.) Blanco.